Condemned or Not to Die? Gene Polymorphisms Associated With Cell Death in Pemphigus Foliaceus - Bumiller-Bini, Valéria; Cipolla, Gabriel Adelman; Spadoni, Mariana Basso; Augusto, Danillo Gardenal; Petzl-Erler, Maria Luiza; Beltrame, Marcia Holsbach; Boldt, Angelica Beate Winter (Frontiers in Immunology, 2019)
Pemphigus foliaceus (PF) is an autoimmune skin blistering disease that occurs sporadically across the globe and is endemic in Brazil. Keratinocyte adhesion loss (acantholysis) is associated with high levels of anti-desmoglein 1 IgG autoantibodies, but the role of cell death is poorly understood in PF. Current evidence disqualifies apoptosis as the major cell death mechanism and no other process has yet been investigated. To approach the role of the variation in genes responsible for cell death pathways in pemphigus susceptibility, we systematically investigated the frequencies of 1,167 polymorphisms from genes encoding products of all 12 well-established cell death cascades (intrinsic and extrinsic apoptosis, necrosis, necroptosis, ferroptosis, pyroptosis, parthanatos, entotic, NETotic, lysosome-dependent, autophagy-dependent and immunogenic). By multivariate logistic regression, we compared allelic and genotypic frequencies of 227 PF patients and 194 controls obtained by microarray hybridization. We found 10 variants associated with PF (p < 0.005), belonging to six cell death pathways: apoptosis (TNF, TRAF2, CD36, and PAK2), immunogenic cell death (EIF2AK3, CD47 and SIRPA), necroptosis (TNF and TRAF2), necrosis (RAPGEF3), parthanatos (HK1) and pyroptosis (PRKN). Five polymorphisms were associated with susceptibility: TNF rs1800630*A (OR = 1.9, p = 0.0003), CD36 rs4112274*T (OR = 2.14, p = 0.0015), CD47 rs12695175*G (OR = 1.77, p = 0.0043), SIRPA rs6075340*A (OR = 2.75, p = 0.0009) and HK1 rs7072268*T (OR = 1.48, p = 0.0045). Other five variants were associated with protection: TRAF2 rs10781522*G (OR = 0.64, p = 0.0014), PAK2 rs9325377*A (OR = 0.48, p = 0.0022), EIF2AK3 rs10167879*T (OR = 0.48, p = 0.0007), RAPGEF3 rs10747521*A (OR = 0.42, p = 0.0040) and PRKN rs9355950*G (OR = 0.57, p = 0.0004). Through functional annotation, we found that all associated alleles, with the exception of PRKN rs9355950*G, were previously associated with differential gene expression levels in healthy individuals (mostly in skin and peripheral blood). Further functional validation of these genetic associations may contribute to the understanding of PF etiology and to the development of new drugs and therapeutic regimens for the disease.